Acute Effects of Ischemic Intra-Conditioning on 30 m Sprint Performance - Fostiak, Krzysztof; Bichowska, Marta; Trybulski, Robert; Trabka, Bartosz; Krzysztofik, Michal; Rolnick, Nicholas; Filip-Stachnik, Aleksandra; Wilk, Michal (International journal of environmental research and public health, 2022)
The present study aimed to evaluate the effects of ischemic intra-conditioning applied during rest intervals on 30 m sprint performance. Thirty-four trained male (n = 12) and female (n = 22) track and field and rugby athletes volunteered to participate in the study (age = 19.6 ± 4 years; training experience = 5.3 ± 1.9 years). In a randomized and counterbalanced order, participants performed six sets of 30 m sprints under three different testing conditions: without ischemic intra-conditioning, and with ischemic intra-conditioning at 60% or 80% arterial occlusion pressure applied bilaterally before the first trial of the sprint and during the rest periods between all sprint trials. During experimental sessions, subjects perform 6 × 30 m sprints with a 7 min rest interval between attempts. The cuffs were applied following a 1 min rest period and lasted for 5 min before being released at the 6th minute to allow for reperfusion (1 min + 5 min ischemic intra-conditioning + 1 min reperfusion). The two-way repeated measures ANOVA did not show statistically significant condition × set interaction for time of the sprint (p = 0.06; η2 = 0.05). There was also no main effect of ischemic intra-conditioning for any condition (p = 0.190; η2 = 0.05). This study indicates that ischemic intra-conditioning did not enhance the performance of 30 m sprints performed by athletes. However, ischemic intra-conditioning did not decrease performance either.
Keywords: Female; Rest; Adolescent; mužské pohlaví; training; testing; mladý dospělý; lehká atletika; Humans; performance; lidé; sportovci; sportovní výkon; ženské pohlaví; Athletic Performance; Track and Field; Athletes; Young Adult; running; odpočinek; Male; mladiství